2018
DOI: 10.1017/s1049023x18001103
|View full text |Cite
|
Sign up to set email alerts
|

Mass-Gathering Medical Care Provided by a Collegiate-Based First Response Service at an Annual College Music Festival and Campus-Wide Celebration

Abstract: BackgroundThere is insufficient research on medical care at mass-gathering events (MGEs) on college and university campuses. Fun Day is an annual celebratory day held at Skidmore College (Saratoga Springs, New York USA), a small liberal arts college in the Northeastern United States. Fun Day is focused around an outdoor music festival; students also congregate and celebrate throughout the surrounding campus. To improve care and alleviate strain on local resources, a model was developed for the provision of eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…2 With these definitions in mind, it is clear that MG events intrinsically have the potential for significant health risks for all involved and pose a challenge for those involved in the provision of medical care. 3 When approving an MG, the government guarantees that the medical support at this event meets national standards of quality of care and response time. Belgian law obliges municipal governments to identify and analyze the risks involving the MG event.…”
Section: Introductionmentioning
confidence: 99%
“…2 With these definitions in mind, it is clear that MG events intrinsically have the potential for significant health risks for all involved and pose a challenge for those involved in the provision of medical care. 3 When approving an MG, the government guarantees that the medical support at this event meets national standards of quality of care and response time. Belgian law obliges municipal governments to identify and analyze the risks involving the MG event.…”
Section: Introductionmentioning
confidence: 99%
“…Our study is the first to examine the medical emergencies within the visitor population of a large music festival over 7 consecutive years. To our knowledge, only one study has investigated a college music festival over a 4-year period [10].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies reported patient presentations at a given music festival for only 1 or 2 years [6][7][8][9][10], and/or focus on special topics, such as the mental health of visitors or drug use [6,7,11,12]. Longitudinal observations from music festivals over several consecutive years are sparse [10]. It is unclear (yet important for predicting medical demand) if the epidemiology of health related events at an annual music festival changes over the course of several years.…”
Section: Introductionmentioning
confidence: 99%
“…They pose a challenge for those responsible for providing in-event- health services (IEHS). 1 The World Health Organization (WHO) defines a MG as “a gathering of persons at a specific location for a specific purpose for a defined period of time” with “the number of people attending to be sufficient to strain the planning and response resources of the community, state or nation hosting the event.” 2 The straining of planning and response resources is further emphasized by Arbon who adds that a mass gathering is “a situation during which crowds gather and where there is the potential for a delayed response to emergencies because of the limited access to patients.” 3 Starting in 2006, municipal governments in Belgium have been obliged to perform a risk assessment involving each MG on its territory. 4 All too often, the variables used for this risk assessment stem from a police or firefighter service risk assessment and do not meet the medical needs for a MG.…”
Section: Introductionmentioning
confidence: 99%